Morphological changes of ZnO nanostructures upon addition of Trisodium Citrate (Na3C6H5O7) at different reaction temperatures - Aqilah, Kamaruzaman; Nurul Akmal, Che Lah (Penerbit UMP, 2021)
Due to its interesting physical and chemical properties, zinc oxide (ZnO) is considered one of the front runners of numerous metal oxide semiconductors. In this paper, ZnO nanostructure are synthesised by hydrothermal method with trisodium citrate (TC) as the emulsfying agent. The mean diameetr of ZnO nanostructure are observed with increment of reaction temperature. The mean size results into no change to mean diameter upon increment of reaction temperature but the cumulative frequencies of size distribution showing ZnO nanostructure synthesised in higher temperature to have narrower size distribution. The addition of TC also results into much smaller ZnO nanostructure with mean diameter 8nm.